Subjective assessment of changes in life during covid-19 pandemic: comparison of polish and ukrainian adults - Szepietowska, Ewa Małgorzata; Zawadzka, Ewa; Filipiak, Sara (My University, 2022)
Purpose. The first stage of the COVID-19 pandemic was associated with the growing sense of massive trauma and loss. The current research suggests that the past two years of the pandemic are perceived in terms of both losses and gains. The study aimed to compare opinions expressed by adult Poles and Ukrainians, about changes in various spheres of life resulting from the two years of the pandemic. Methods. The survey was carried out online using COVID-19 Sense of Life Changes Questionnaire. Responses were provided by 270 Poles and 109 Ukrainians. The participants were expected to report whether and in what way (positive, negative or none) specific areas of their life changed during the pandemic. Results. Respondents from Poland and Ukraine noticed both negative and positive changes in various areas of life, resulting from the pandemic. Opinions related to many issues expressed by the two groups were similar, however respondents from Ukraine tended to assess the two-year period of the pandemic in more positive terms (as a time of minor negative changes or time that did not change much in their lives). Conclusions. Our findings reflect the fact that there is a change in emotional and knowledge-based evaluation of the two-year pandemic. Further research should look into social and cultural contexts which may explain psychological response to COVID-19 pandemic.
Keywords: COVID-19 pandemic; subjective assessment of changes in life; Poland; Ukraine; 159.99